MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR IPA MELALUI MODEL DISCOVERY LEARNING SISWA KELAS IV SD NEGERI 1 SAMALANGA - Misrina Misrina (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh bekerjasama dengan PW PERGUNU Aceh, 2022)
The learning process in science learning focuses on providing direct learning experiences to students so that they are able to develop competencies in order to understand the natural surroundings scientifically. Therefore, learning process an important role in improving student learning outcomes, so that student competencies develop optimally. The research aims to improve the activities and learning outcomes of science through discovery learning models of grade IV students atSD Negeri 1 Samalanga. Subjects of this research were 26 students. This research is a classroom action research, which is carried out in two cycles. The results of the research are in the form of activities and student learning outcomes. Based on observation data and final test results in cycle 1, the data obtained for student learning activities with a percentage of 78.18% while the completeness of learning outcomes is only 65.38%. This means that both activities and student learning outcomes in cycle 1 have not reached completeness. Therefore, the researcher continued the research to cycle 2. The acquisition of activity data and learning outcomes in cycle 2 increased where the percentage of mastery learning activities increased to 92.72% while the percentage of learning outcomes reached 88.46%. Thus there is an increase in science learning activities and outcomes through the discovery learning model of grade IV students at SD Negeri 1 Samalanga